Survey of marine natural product structure revisions: a synergy of spectroscopy and chemical synthesis - Suyama, Takashi L. (2011)
The structural assignment of new natural product molecules supports research in a multitude of disciplines that may lead to new therapeutic agents and or new understanding of disease biology. However, reports of numerous structural revisions, even of recently elucidated natural products, inspired the present survey of techniques used in structural misassignments and subsequent revisions in the context of constitutional or configurational errors. Given the comparatively recent development of marine natural products chemistry, coincident with the modern spectroscopy, it is of interest to consider the relative roles of spectroscopy and chemical synthesis in the structure elucidation and revision of those marine natural products which were initially misassigned. Thus, a tabulated review of all marine natural product structural revisions from 2005 to 2010 is organized according to structural motif revised. Misassignments of constitution are more frequent than perhaps anticipated by reliance on HMBC and other advanced NMR experiments, especially considering the full complement of all natural products. However, these techniques also feature prominently in structural revisions, specifically of marine natural products. Nevertheless, as is the case for revision of relative and absolute configuration, total synthesis is a proven partner for marine, as well as terrestrial, natural products structure elucidation. It also becomes apparent that considerable ‘detective work’ remains in structure elucidation, in spite of the spectacular advances in spectroscopic techniques.